Empowering women ex-migrant workers: Transforming lives through sustainable ecoprint training in Sidomulyo Village - Antika, Elly; Susmiati, Yuana; Andini, Dessy Putri (P3M Politeknik Negeri Jember, 2025)
Sidomulyo Village, located in Silo District, Jember Regency, is an area with significant tourism potential due to its proximity to the largest coffee plantation in Jember. The village offers various attractions, including Sendang Natural Tourism, wooden houses, a cycling track overlooking Mount Kumitir, and opportunities for milk and coffee farming, positioning it as a prospective tourist village. However, despite these natural advantages, the village faces economic challenges due to the high number of returning migrant workers with limited employment opportunities. This study aims to explore community empowerment through skill development, particularly in ecoprint craft production, as an alternative economic opportunity. The participatory approach involved training sessions on ecoprint techniques, utilizing abundant natural materials such as leaves, flowers, and tree bark. Additionally, business mentoring and assistance were provided to help participants develop small enterprises and increase their income. The results indicate a significant improvement in skills, with 85% of participants demonstrating proficiency in ecoprint techniques and a readiness to start entrepreneurial ventures. The initiative was further supported by local government efforts, including internet access for digital marketing and business mentoring programs. Despite these positive outcomes, the study faced challenges such as limited initial knowledge among participants, the need for continuous mentoring, and market access constraints for eco-friendly products. Addressing these challenges requires sustained support, including stronger partnerships with stakeholders and expanded marketing strategies. This study highlights the importance of skill-based empowerment as a strategy for economic resilience in rural communities.